Pengaruh Sikap Kerja Dan Organizational Learning Terhadap Kinerja Pegawai - Syifa Nur Auliah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The background of this research is that the performance of employees of the Ciamis Regency Investment and One-Stop Services Office is still not optimal. This is thought to be caused by not optimal work attitudes and implementation of organizational learning. The purpose of this study was to find out 1) The effect of work attitude on employee performance at the Investment and One-Stop Services Office of Ciamis Regency; 20 The effect of organizational learning on employee performance at the Investment and One-Stop Services Office of Ciamis Regency; 3) The influence of work attitudes and organizational learning on employee performance at the Investment and One-Stop Services Office of Ciamis Regency. In this study used a survey method with a quantitative data approach. The population in this study were ASN employees at the Ciamis Regency Investment and One-Stop Services Office, totaling 35, so the authors took samples using a saturated sampling technique so that the number of samples in this study were 35 people. Analysis was carried out on the data collected both from the results of observations, interviews, and questionnaires. The stages of data analysis begin with validity, reliability and verification/quantitative data analysis. The results of the study show that: 1) There is a positive and significant effect of work attitude on employee performance at the Investment and One-Stop Services Office of Ciamis Regency. This means that the better the work attitude at the Ciamis Regency One Stop Investment and Integrated Services Service, the employee's performance will increase; 2) There is a positive and significant effect of organizational learning on employee performance at the Investment and One-Stop Services Office of Ciamis Regency. This means that the better the organizational learning at the Investment and One-Stop Service Office of Ciamis Regency, the employee's performance will increase; 3) There is a positive and significant effect of work attitude and organizational learning on employee performance at the Investment and One-Stop Services Office of Ciamis Regency. This means that the better the work attitude and organizational learning at the Investment and One-Stop Services Office of Ciamis Regency, the employee's performance will increase.